2014
DOI: 10.1186/1471-227x-14-22
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of in-hospital trauma deaths in a Brazilian university hospital

Abstract: BackgroundThe analysis of patterns of trauma deaths may improve the evaluation of a trauma system and identify areas that may benefit from more resources. The objective of this study was to analyze the epidemiology of trauma deaths in a Brazilian university hospital in order to assess the profile of these fatalities over a 16-year period.MethodRetrospective study of time series using database records. The research subjects were in-hospital deaths from external causes during the years 1995, 2000, 2005 and 2010.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 28 publications
0
18
0
8
Order By: Relevance
“…A study from Brazil reported that the proportion of deaths from motorcycle accidents increased by 820% between 1996 and 2007 [5]. Another study also showed that there was a significant increase in the number of deaths of motorcycle riders over time, increasing from 7.3% in 1995 to 31.5% in 2010 [6].…”
Section: Introductionmentioning
confidence: 88%
“…A study from Brazil reported that the proportion of deaths from motorcycle accidents increased by 820% between 1996 and 2007 [5]. Another study also showed that there was a significant increase in the number of deaths of motorcycle riders over time, increasing from 7.3% in 1995 to 31.5% in 2010 [6].…”
Section: Introductionmentioning
confidence: 88%
“…About 60% of deaths occurred within less than 24 h. TBI was the cause of death in 56.3%, hemorrhage in 18.1% and multiple organ failure in 17.1% of cases. Mean ISS for patients with signs of life was 26.4 ± 9.0; mean RTS was 5.24 ± 2.05, and only 25.8% had a probability of survival less than 0.5 [22] . Leow et al analyzed the effect of race and ethnicity on trauma mortality in patients with an ISS of 9 in a study coming from a 1 300-bed trauma center, from Singapore [23] .…”
Section: Discussionmentioning
confidence: 98%
“…During the study period a reduction for TBI and an increase for multiple organ failure were observed [21] . Trajano et al evaluated the epidemiology of trauma deaths in a Brazilian university hospital [22] . Out of 467 cases, 30.4% were classified as death on arrival.…”
Section: Discussionmentioning
confidence: 99%
“…Arslan ve arkadaşları travmaya bağlı ölümlerde en sık nedenin travmaya bağlı beyin yaralanması olduğunu bildirmişlerdir 9. Trajona, Gunst, Hamzeh ve arkadaşları travmaya bağlı ölümlerde en sık nedenin kafa travması olduğunu bildirmişlerdir 11,12,14. Evans ve arkadaşları yüksek enerjili travmaya bağlı ölümlerde en sık nedenlerin %33 oranında santral sinir sistemi ve %33 oranında hemorajiye bağlı olduğunu bildirmişlerdir 13.…”
unclassified